Validating school-based measures of educational disadvantage in Ireland - Gilleece, Lorraine; McHugh, Gráinne (Education Policy Analysis Archives, 2022)
Reducing the socio-economic achievement gap is a key goal of education policy internationally. Since 2017, the stated intention in Ireland is to use the Pobal HP Deprivation Index to identify schools serving high proportions of disadvantaged students. In spite of this, little published research has compared the performance of the HP index to richer survey measures from large-scale educational assessments or examined its association with educational achievement at primary or second level. This paper aims to assess the validity and fitness for purpose of the HP index for use in identifying schools serving high concentrations of socio-economically disadvantaged students. Analyses draw on Ireland’s Program for International Student Assessment (PISA) 2018 dataset matched with administrative data. Findings show a strong correlation between school-average HP and other socio-economic measures examined. However, about one-in-five schools are identified as potential ‘false positives’ or ‘false negatives’ when school-average HP is used for identification purposes. Also, school-average HP explains less variance in reading achievement than other variables considered. Conclusions recognize the benefits of the HP index but emphasize the need for ongoing examination of the most appropriate methods of identification.